APLIKASI THEORY OF PLANNED BEHAVIOR UNTUK MEMPREDIKSI PERILAKU MAHASISWA MEMBELI LAPTOP LENOVO (Studi Kasus: Mahasiswa FE- Unika Santo Thomas SU) - Tamba, Darwis (UNIKA Santo Thomas, 2017)
The purpose of this study to analyze the application of theory of planned behavior to predict student behavior to buy Lenovo laptops. Benefits This study provides input to other researchers in conducting further research on the same topic and add insight and knowledge of researchers in the field of consumer behavior, especially about the application of theory of planned behavior to predict student behavior to buy a laptop lenovo. Total sample 96 respondents, data collection method through questioner and documentation, Descriptive analysis technique. The results showed based on the observed variables that: Attitudes, subjective norms and control behaviors felt by students FE Unika St. Thomas SU on average gives a positive influence on the behavior to buy branded Lenovo laptops. This is in line with the behavioral interest equation = BI = 0.44Ab + 0.16SN + 0.40PC. That is, the behavior of FE Unika St. Thomas SU to buy larger brand Lenovo laptops is influenced by attitudes of 0.44 (44%) than perceived behavioral controls of 0.40 (40% and subjective norms 0.16 (16%)). attributes that students place to win competition and preferably, laptop manufacturers increase the influence of subjective norms and perceived behavioral control by offering various benefits to consumers